2016
DOI: 10.3201/eid2212.151968
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Case of West Nile Neuroinvasive Disease in Bulgaria

Abstract: To the Editor: West Nile virus (WNV) is a mosquitoborne flavivirus. Approximately 80% of human infections are asymptomatic, 10%–20% are characterized by an acute febrile illness, and <1% by involvement of the central nervous system (West Nile neuroinvasive disease). Sporadic human cases and small outbreaks of West Nile fever were reported in Europe until the mid-1990s, when the first large outbreak occurred in Romania in 1996.\ud \ud Since then, and especially in recent years, sporadic human cases and outbreak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Nevertheless, they showed that WNV is widespread in the country. The highest WNV seroprevalence rate was detected in Sofia Province, where the first confirmed neuroinvasive case was described in 2015 [36] and an additional case was confirmed in 2016. WNV IgM antibodies were detected in people only from this district, giving a certainty that it is a "hot spot," and more cases from this area could be expected in the future.…”
Section: A Nationwide Seroprevalence Screening For West Nile Virus Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, they showed that WNV is widespread in the country. The highest WNV seroprevalence rate was detected in Sofia Province, where the first confirmed neuroinvasive case was described in 2015 [36] and an additional case was confirmed in 2016. WNV IgM antibodies were detected in people only from this district, giving a certainty that it is a "hot spot," and more cases from this area could be expected in the future.…”
Section: A Nationwide Seroprevalence Screening For West Nile Virus Inmentioning
confidence: 99%
“…First in 2015, a few probable WNV human cases appeared in Bulgaria. Then, one confirmed WNV neuroinvasive infection was described [36]. The causative strain belonged to WNV lineage 2, closely related to Greek strains that caused Vector-Borne Infections in Bulgaria DOI: http://dx.doi.org /10.5772/intechopen.81916 the largest outbreak of WNV in Europe 2010-2013 [37] and also close to the WNV that caused outbreak in Hungary in 2008, when the WNV lineage 2 emerged for the first time outside Africa [38].…”
Section: West Nile Fever 41 Introductionmentioning
confidence: 99%
“…There was no further detection until 2015 when 3 human cases were reported. Phylogenetic analysis showed that the virus was closely related to the WNV lineage 2 strain isolated in Greece [27]. In 2014, also WNV lineage 2, similar to the Greek isolate, was detected in the brain of a horse with severe clinical signs in Bursa region in eastern Turkey [28], but so far no human cases have been reported.…”
Section: Flaviviruses (Genus Flavivirus Family Flaviviridae)mentioning
confidence: 99%
“…Determinants of susceptibility to West Nile Virus (WNV). Resistance and susceptibility to WNV infection result from exposure history and immune status including immunosuppression, cardiovascular disease, chronic renal disease and hepatitis C virus infection [7,[21][22][23]. Individual susceptibility also derives from host factors such as single nucleotide polymorphisms (SNPs) in immune response genes [5,[24][25][26][27][28][29][30], and control of cytokine responses to infection [32][33][34][35][36][37] (a).…”
Section: Host Factors Are a Risk For Severe West Nile Virus Infectionmentioning
confidence: 99%